ACTUAL PROBLEMS AND ACHIEVEMENTS OF THE UNIVERSE - Turayeva , Nozima; Urinboyeva, Kumushoy Sultanbek qizi (Educational Research in Universal Sciences, 2023)
Cosmogony describes the origin and evolution of the galaxy, Cosmology problems of cosmogony and geometric structure of the galaxy, It deals with the coming into being NASA’s space exploration project. Advances in modern astronomy.